Worry and ruminative brooding: associations with cognitive and physical health in older adults - Morse, Rachel M.; Koutsoubelis, Freya; Whitfield, Tim; Demnitz-King, Harriet; Ourry, Valentin; Stott, Josh; Chocat, Anne; Devouge, Eglantine Ferrand; Walker, Zuzana; Klimecki, Olga; Collette, Fabienne; Chetelat, Gael; et al. (Frontiers in Psychology, 2024)
Mental health conditions are associated with cognition and physical function in older adults. We examined whether worry and ruminative brooding, key symptoms of certain mental health conditions, are related to subjective and/or objective measures of cognitive and physical (cardiovascular) health. We used baseline data from 282 participants from the SCD-Well and Age-Well trials (178 female; agemean=71.1 years). We measured worry and ruminative brooding using the Penn State Worry Questionnaire and the Ruminative Response Scale-brooding subscale. We assessed subjective physical health using the WHOQOL-Bref physical subscale, and objective physical health via blood pressure and modified versions of the Framingham Risk Score and Charlson Comorbidity Index. With subjective and objective cognition, we utilized the Cognitive Difficulties Scale and a global composite (modified Preclinical Alzheimer's Cognitive Composite, PACC5, with the Wechsler Adult Intelligence Scale-IV, category fluency, Mattis Dementia Rating Scale-2, and either the California Verbal Learning Test or the Rey Auditory Verbal Learning Test). We conducted linear regressions, adjusted for education, age, sex and cohort. Worry and brooding were negatively associated with subjective physical health (worry: β=-0.245, 95%CI -0.357 to -0.133, p<0.001; brooding: β=-0.224, 95%CI -0.334 to -0.113, p<0.001) and subjective cognitive difficulties (worry: β=0.196, 95%CI 0.091 to 0.302, p<0.001; brooding: β=0.239, 95%CI 0.133 to 0.346, p<0.001). We did not observe associations between worry or brooding and any measure of objective health. Worry and brooding may be common mechanisms associated with subjective but not objective health. Alternatively, cognitively unimpaired older adults may become aware of subtle changes not captured by objective measures used in this study. Interventions reducing worry and brooding may promote subjective physical and cognitive health; however, more research is needed to determine causality of the relationships.